DAKWAH NABI MUHAMMAD DI MADINAH (Analisis Keberhasilan Dakwah Nabi dalam Tinjauan Sosiologi) - Muhamad Faizul Amirudin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2018)
Da'wah of the Prophet Muhammad in Medina achieved success with a relatively short time. The missionary strategy carried out by the Prophet by establishing a mosque as a center of activity and worship, uniting the tribes of Aus and Kharaj, Muslims with non-Muslims, brothering the Muhajirites and Ansar and the charter of Medina which became important documents in the establishment of the State of Medina. The social changes that occur in the Medina community as an indicator of the success of prophetic preaching from a sociological review that the prophet has succeeded as an Agent of Change or Da'I changed the social order and values and the system of government and economy in Madina.